"Status Quo" of Malay Linguistics Studies: A Bibliometric Analysis - Yaqin, Lalu Nurul; Badriyah Yusof; Ashrol Rahimy Damit (Journal of Language and Literature Studies, 2024)
The study of Malay linguistics is a dynamic and intellectually engaging pursuit that provides valuable insights into the nuanced subtleties of one of the world’s most widely spoken languages. The study of the Malay language holds a significant place in the extensive field of linguistic research because it reflects the diverse linguistic and cultural legacy of the Malay Archipelago. The study explores and analyses Malay linguistic studies conducted over the past two decades, examining trends, types of studies, research methodologies, prevalent themes, and author networks within Malay linguistics. The study employs bibliometric analysis of articles retrieved from the Scopus database using the keyword "Malay Linguistic." Utilising Vosviewer software, it identifies key trends and essential research themes within Malay linguistics. The findings revealed several key points. Firstly, publication trends in Malay linguistics varied over two decades, peaking at 91 publications in 2023, with stability observed from 2004 to 2009. This dynamic reflects evolving research interests with 724 publications. Major publishing venues were predominantly international journals in Malaysia and beyond the Malay Archipelago. Secondly, qualitative research was the primary method, often complemented by interdisciplinary and mixed-method approaches. Thirdly, common themes included Malay communities, dialect variations, identity, language structure, and applied linguistics. Fourthly, the author network in Malay linguistics remains interconnected, primarily among researchers from the Malay Peninsula. The trend of study themes in Malay linguistics has remained relatively stable, showing continuity with the status quo of the previous patterns. However, there has been a noticeable development in publication venues and author networks during this period.